ANALISIS DAN PERANCANGAN SISTEM INFORMASIKEUANGAN USAHA DAGANG BETRA BEBEK OGAN ILIR SUMSEL - Evi Yulianti; Dasrial Dasrial (UNIVERSITAS INDO GLOBAL MANDIRI)
A Financial Information System has an important role in developing and improvingBetra Bebek Ungkap Entreprises Ogan Ilir in South Sumatra. In analyzing the data, especially the financial which not computerized, product transaction receipt, the sale of product and delivering betra bebek were saved, thus the data analysis was not effective and the errors happened frequently that cause the loss of the data. This study analyzed and designedthe financial information systems to handle the problems that occur on the system used nowdays. The results obtained by the construction of financial information served as a system for processing and making financial reports, so that the information system was expected to process financial data processing to be more accurate, fast and timely.Keywords: Analysis, Design of Information Systems Financial